Criminal psychology in action: a project based approach - Canter, David (Routledge, 2025)
Criminal Psychology in Action provides a practical, hands-on introduction to criminal psychology through unique projects for students, illustrating the many ways research into crimes and criminals can be conducted. It also provides an overview of many individual and social psychological theories of criminality